Band-gap engineering of ZnO1−xSx films grown by rf magnetron sputtering of ZnS target. (November 2015) - Khomyak, V.; Shtepliuk, I.; Khranovskyy, V.; Yakimova, R.
Abstract: Structural and optical properties of ZnO1−x Sx (0 ≤  x ≤  1.0) thin films grown onto sapphire substrates ( ≿ -Al2 O3 ) at 300 °C by radio frequency (rf) magnetron sputtering of ZnS ceramic target are studied. A possibility of purposeful controlling sulfur content and, as consequence, ZnO1−x Sx band gap energy via changing the ratio of the partial pressures of argon and oxygen are revealed. Linear dependence of ZnO lattice parameter c on S content suggests that structural properties of single-phase ternary alloys in the composition range between ZnO and ZnS obey Vegard's law. The mechanisms of influence of gas mixing ratio on film growth and band gap energy are discussed. Cu(In, Ga)Se2 (CIGS)-based heterojunction solar cells with ZnO1−x Sx buffer layers were fabricated by one-cycle magnetron sputtering procedure. Electrical characteristics of Cd-free devices are comparable to those of CdS-containing photovoltaic heterostructures, thereby indicating prospects of using ZnO1−x Sx layers for fabrication of CIGS solar cells. Highlights: Single phase ZnO1−x Sx films (0 ≤ x ≤ 1) are grown by rf magnetron sputtering. Composition of alloys and band gap energy are driven by gas mixing ratio. Regimes of formation of ZnO1−x Sx films are governed by Ar/O2 ratio. Bowing parameter as large as 3.5 eV is determined. CIGS solar cells with ZnO1−x Sx buffer layers are fabricated and characterized.